KONSEP HARTA DALAM PANDANGAN EKONOMI ISLAM - Muthmainnah Muthmainnah (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2016)
Islam is a religion whose teachings were revealed by Allah to mankind through Prophet Muhammad as the messenger, which in essence bringing teachings not only on one side, but on the various facets of human life. Islam is very concerned with the rights of each individual, because it is one of the objectives of sharia which is to maintain the property of each individual, because the property is an asset of every individual in the form of material that support the sustainability aspects of the life of a servant in the course of worship to God. SWT. related to the above, the title of this research is the concept of property in view of Islamic Economics. The study is a literature review that coverage discussion is that the concept of property in the view of Islamic economics, ownership patterns based on the view of Islam, the ownership of which is protected by Islam. Based on the study conducted, the results of this discussion is the concept of property and ownership in the teachings of Islam, at its core is fully aware that the ultimate owner of everything is God Almighty, applicable human as caliph, only the temporary owner of what he has. Therefore, in every economic action or in an attempt to acquire wealth, people have to go through the road blessed by law both in sourcing, process or utilization of such property. Because at intinnya everything possessed by man will be held accountable by Allah in the Hereafter complaint.